"Transient Communities": How Central American Transit Migrants form Solidarity Without Trust. Issue 5 (20th October 2022) - Díaz de León, Alejandra
ABSTRACT: Migrants in transit through Mexico are often separated from their social networks; this increases the risks associated with an already precarious process. Through eight months' worth of ethnography and 40 in-depth interviews conducted on the southern and northern borders of Mexico, this article seeks to understand how migrants compensate for their lack of social networks and find emotional and economic support and information while in transit. The research found that, for Central American transit migrants, the most efficient way to access the necessary resources to move was by forming a community en route – a "transient community." This community facilitates cooperation and the sharing of resources between its members and other migrants who they do not know and do not trust. It provides: a shared identity created by a common struggle; solidarity and resources; and information and "rules of the game." The solidarity and the sharing of information and resources facilitate the journey of undocumented migrants and reduce its costs. This study shows that transit migrants form new social arrangements that overcome the uncertainty and violence of life on the road, and that cooperation and solidarity can exist even among people who mistrust each other and share no common social ties.